2013
DOI: 10.3998/ark.5550190.0014.301
|View full text |Cite
|
Sign up to set email alerts
|

Quinine-catalyzed enantioselective tandem conjugate addition/intramolecular cyclization of malononitrile and 1,4-dien-3-ones

Abstract: An organocatalytic tandem conjugate addition / intramolecular cyclization of malononitrile and conformationally restricted 1,4-dien-3-ones has been developed. A series of cinchona alkaloids and their derivatives were examined as the catalysts. Quinine was found to be the most efficient catalyst in the absence of any additive. The reaction gave 2-amino-4H-pyrans with high yield and excellent enantiopurity using only 5 mol% quinine as the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The transformation was limited to one example of cyclohexadienone substrate but the reaction was successfully extended to diversely substituted conformationally restricted dienones producing enantioenriched piperidine derivatives 114 a–f , tetrahydropyrans 114 g or other functionalized pyrans 114 h–i . The authors demonstrated that this reaction can also be promoted by quinine as an organocatalyst [60] …”
Section: Functionalization Of 26‐dialkylidenecyclohexanonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation was limited to one example of cyclohexadienone substrate but the reaction was successfully extended to diversely substituted conformationally restricted dienones producing enantioenriched piperidine derivatives 114 a–f , tetrahydropyrans 114 g or other functionalized pyrans 114 h–i . The authors demonstrated that this reaction can also be promoted by quinine as an organocatalyst [60] …”
Section: Functionalization Of 26‐dialkylidenecyclohexanonesmentioning
confidence: 99%
“…The authors demonstrated that this reaction can also be promoted by quinine as an organocatalyst. [60] Du and Gao took advantage of the bifunctional activity of the tertiary amine-squaramide catalyst in the reaction of malononitrile with the conformationally restricted dienones 115 (Scheme 35). [61] After a careful optimisation, the organocatalyst cat-46 was investigated in the reaction of malononitrile with carbocycles such as bisarylidenecyclohexanone 115 produce the dispirane 119 (Scheme 36).…”
Section: Functionalization Of 26-dialkylidenecyclohexanonesmentioning
confidence: 99%